Syphilis in riverine communities: prevalence and associated factors - Wynne Pereira Nogueira; Matheus Figueiredo Nogueira; Jordana de Almeida Nogueira; Maria Eliane Moreira Freire; Elucir Gir; Ana Cristina de Oliveira e Silva (SciELO, 2022)
Abstract Objective: To estimate the prevalence of syphilis and associated factors in riverine communities. Method: This is a cross-sectional and analytical study carried out with 250 riverside dwellers living in five communities in the city of João Pessoa, state of Paraíba. Data were collected through interviews and rapid screening tests to investigate syphilis. Bivariate, logistic regression and weight of evidence analysis were performed to identify the association between risk factors and behavior variables and rapid test positivity. Results: he prevalence of syphilis was 11.6% (95%CI: 7.5-15.6). Riverside dwellers who have a previous history of Sexually Transmitted Infection (OR 8.00; 95%CI: 2.76-23.2), history of imprisonment (OR 7.39; 95%CI: 1.61-33.7) and who reported having more than two sexual partners in the last 12 months (OR 4.31; 95%CI: 1.55-11.9) were more likely to be positive for syphilis. Conclusion: High prevalence of syphilis among riverside dwellers and the presence of behavioral factors that increase vulnerability to acquiring the infection. The need to invest in preventive and screening strategies for syphilis in populations considered vulnerable is highlighted.